Discoveries India. Land of the Maharajas [videorecording (DVD)]. (Bennett Watt Media, 2008)
Perhaps the most colorful region in India, Rajasthan is a land graced with impenetrable forts, spectacular palaces and waves of sand dunes and serene lakes. This region represents a mystique unequaled in the world for its amazing diversity in heritage, culture and desert expanse.